Emerging Resistance to Albendazole in Soil-Transmitted Helminths - Widiastara, Antonio Ayrton; Lucas, Amalia Margaretha; da Gama, Laura Boavida; Guterres, Basiraldo Baru; Ferreira, Esmeraldito; Gomes Fernandes, Sergio Herminio (Current Internal Medicine Research and Practice Surabaya Journal, 2025)
Soil-transmitted helminths (STHs) are significant pathogens affecting approximately 1.5 billion people globally, with the highest prevalence in sub-Saharan Africa, South America, and Asia. This study examined the effectiveness of albendazole, a widely used anthelminthic drug, in treating STH infections, particularly focusing on its potential resistance. Despite its effectiveness in many cases, recent studies have indicated a concerning trend of reduced efficacy, particularly against species such as Trichuris trichiura. This study reviewed literature from the past decade, identifying key studies that demonstrate a decline in albendazole’s effectiveness across various populations, including school-aged children in multiple regions. The findings proposed that while albendazole remains the primary treatment option, its effectiveness varies significantly based on geographic and demographic factors, raising concerns about the emergence of drug resistance. This study emphasizes the need for ongoing monitoring and potential pharmacological combinations to enhance treatment efficacy and address the threat of resistance. Ultimately, the research highlights the complexity of managing STH infections and the necessity for tailored intervention strategies.   Highlights: 1. Although albendazole is a commonly used medication for soil-transmitted helminths (STHs), its efficacy seems to be waning, thereby requiring additional research to analyze potential resistance. 2. Many studies have pointed out a decreased efficacy of albendazole, despite none having verified resistance, indicating that the medication remains efficacious in specific groups, geographical areas, and dosage regimens where STH infections are prevalent.